Vortex induced aerodynamic forces on a flat plate in ground proximity - Holt, Jennifer C.; Garry, Kevin P. (AIAA, 2016)
Vehicle underbody longitudinal vortices can have a significant effect on the aerodynamic loads experienced by a body in close ground proximity. A series of wind tunnel tests at a nominal Reynolds number of 2.26 x 106 ,were carried out to investigate both (i) the influence of a moving ground plane simulation compared to fixed ground and (ii) the effect of relative location and strength of underbody longitudinal vortices on a simple flat plate, at zero incidence, fitted with vane vortex generators. The presence of vortices between the plate and the ground plane serve to reduce the local pressure and generate a negative lift on the plate. The data indicate that an increase in vortex strength (proportional to an increase in vane vortex generator angle, β) increases plate negative-lift coefficient (CL. The lift coefficient becomes more negative with decreasing ground clearance (h/c) for all cases except those for which there is evidence of vortex breakdown (high vane angles and low ground clearance). The variation of negative-lift-to-drag coefficient ratio shows that the overall aerodynamic efficiency is greater for smaller vortex generator angles at the lowest ground clearances. The pitching moment coefficient was found to change from nose down to nose up as ground proximity reduced indicating a movement in the centre of pressure position towards the plate trailing edge.